The Simulium nigritarse subgroup (Diptera: Simuliidae) in Uganda: New species and country records - Krüger, Andreas (Zootaxa, 2016)
Amongst blackfly samples from western Uganda three different morphospecies of the Simulium (Nevermannia) nigritarse Coquillett subgroup were identified. Of these, S. perforatum Fain & Dujardin showed the widest distribution and is reported from Uganda for the first time. In addition, two new species are described: S. bwambanum sp. nov. and S. itwariense sp. nov. Diagnostic characters are the different structures of the pupal cocoon, the configurations of the gill filaments and adult colour features.